Cultural Diversity of Vocal Schools in China - Du Yuling (ХДАК, 2024)
China has rich vocal traditions, giving rise to various “vocal schools” across its vast territory. These schools,particularly within Chinese opera and folk music, reflect unique styles, techniques, and approaches to vocal performance. China has a vast array of regional folk singing traditions, each with its own vocal techniques and styles. These styles are usually connected to specific regions and ethnic groups. China’s vocal schools are a reflection of its vast cultural diversity, with each school rooted in specific regional, historical, and social contexts. Whether through the highly stylized and refined traditions of “Peking” and “Kunqu opera”, the regional folk singing styles, or the emotionally powerful expre sions of “Cantonese opera”, these schools represent the depth and richness of Chinese vocal arts. Each school has developed its techniques for breath control, ornamentation, projection, and emotional expression, ensuring the preser vation of China’s vocal heritage for future generations.
Keywords: оперне мистецтво; музична культура Китаю